Erect Penile Length and Circumference Dimensions of 1, 661 Sexually Active Men in the United States. (1st January 2014) - Herbenick, Debby; Reece, Michael; Schick, Vanessa; Sanders, Stephanie A.
Abstract: Introduction: Penile size continues to receive popular and empirical attention. Little is known about the process of self-measurement and whether the behaviors a man engages in to become erect for self-measurement are associated with his erect penile dimensions. Aims: The article aims to assess men's erect penile dimensions in a study in which the men would presumably be motivated to report accurate information about their penis size; and to explore associations between men's erect penile dimensions, their method of measurement, and their demographics. Methods: Data are from an Internet-based baseline phase of a large prospective daily diary study that compared men's use of a standard-sized condom to men's use of a condom sized to fit their erect penis. Main Outcome Measures: The main outcomes are participant characteristics, activities engaged in during self-measurement process, and self-reported erect penile length and circumference. Results: For this sample of 1, 661 men, the mean erect penile length was 14.15 cm (SD = 2.66; range = 4 to 26 cm), and the mean erect penile circumference was 12.23 cm (SD = 2.23; range = 3 to 19). Participant characteristics were not associated with measured length or circumference. Most men measured their penis while alone, using hand stimulation to become erect. Conclusions: In this sample of men who measured their erect penile length and circumference for the purposes of receiving a condom sized to fit their erect penis, we found a mean erect penile length of 14.15 cm and a mean erect penile circumference of 12.23 cm. The self-reported erect penile dimensions in this study are consistent with other penile dimension research. Also, findings suggest that mode of getting an erection may influence erect penile dimensions. Additionally, how a man becomes erect for self-measurement may be associated with his erect penile length and/or circumference.